Unusual 4H-phase twinned noble metal nanokites - Niu, Wenxin (2019)
Twinning commonly exists in noble metals. In recent years, it has attracted increasing interest as it is powerful to tune the physicochemical properties of metallic nanomaterials. To the best of our knowledge, all the reported twinned noble metal structures exclusively possess the close-packed {111} twinning plane. Here, we report the discovery of non-close-packed twinning planes in our synthesized Au nanokites. By using the bent Au nanoribbons with unique 4H/face-centered cubic)/4H crystal-phase heterostructures as templates, Au nanokites with unusual twinned 4H-phase structures have been synthesized, which possess the non-close-packed {101¯2} or {101¯6} twinning plane. By using the Au nanokites as templates, twinned 4H-phase Au@Ag and Au@PdAg core-shell nanostructures have been synthesized. The discovery of 4H-phase twinned noble metal nanostructures may pave a way for the preparation of metal nanomaterials with unique twinned structures for various promising applications.